Foxp1 regulates cortical radial migration and neuronal morphogenesis in developing cerebral cortex - Li, Xue; Xiao, Jian; Fröhlich, Henning; Tu, Xiaomeng; Li, Lianlian; Xu, Yue; Cao, Huateng; Qu, Jia; Rappold, Gudrun; Chen, Jie-Guang (PLOS ONE, 2015)
FOXP1 is a member of FOXP subfamily transcription factors. Mutations in FOXP1 gene have been found in various development-related cognitive disorders. However, little is known about the etiology of these symptoms, and specifically the function of FOXP1 in neuronal development. Here, we report that suppression of Foxp1 expression in mouse cerebral cortex led to a neuronal migration defect, which was rescued by overexpression of Foxp1. Mice with Foxp1 knockdown exhibited ectopic neurons in deep layers of the cortex postnatally. The neuronal differentiation of Foxp1-downregulated cells was normal. However, morphological analysis showed that the neurons with Foxp1 deficiency had an inhibited axonal growth in vitro and a weakened transition from multipolar to bipolar in vivo. Moreover, we found that the expression of Foxp1 modulated the dendritic maturation of neurons at a late postnatal date. Our results demonstrate critical roles of Foxp1 in the radial migration and morphogenesis of cortical neurons during development. This study may shed light on the complex relationship between neuronal development and the related cognitive disorders.
Gesehen am 22.06.2020